REKOMENDASI GAGASAN NEO-SUTARTO UNTUK UNIVERSITAS SRIWIJAYA (Respon Terhadap Kasus Oknum Mahasiswa Simpatisan ISIS Tahun 2015): Respons Terhadap Kasus Oknum Mahasiswa Simpatisan ISIS Tahun 2015 - Arafah Pramasto (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2019)
The background of this research is an event when some of the students of Sriwijaya University reportedly became supporters of an extremist organization named Islamic State of Iraq and Syria (ISIS) in 2015. The purposes of the research that's using library research are to trace back the root of the event and formulize a thought as a framework of thinking which can be used as prevention against extremism. Through an adoption of Antonio Gramci's epistemological conception about Organic Intellectual as research limitation, the idea of â€œNeo-Sutartoâ€ which consisted by three components : Neo-Sufism, Tarbiya, and Tolerance is founded by the researcher. Neo-Sufism is well-known as a reformed kind of Tasawuf and useful for balancing exoterics and esoterics aspects, while educatively Tarbiya is used to convert a great values of Neo-Sufism within an awareness of intellectuality, and Tolerance is implemented as the result of Sulh-i-Kul or Universal Peace. This research proves that Neo-Starto is eligible to be recommended and implemented in the Sriwijaya University through its steps such as : providing some literatures which contained stramlining of misconseption about Islam, encouraging university mentoring and supervision system towards the emergence of ideologies, holding the tolerance themed socialization, and discussion, and creating a physical sphere of Neo-Sutarto through monumental buildings or entertainment to promote pluralism and peace.